Wind-induced evaporative cooling passive system for tropical hot and humid climate - Moh, T. S. Y.; Jin, J. J. Y.; Wong, L. A.; Tiong, M. C.; Chan, C. K. (Frontiers in Mechanical Engineering, 2023)
Over the years, the desire to have better thermal comfort in terms of living has been extensively discussed and is in high demand, especially in metropolitan cities. Alongside the desired outcomes, air conditioning facilities have been implemented, but they also bring negative consequences, such as a high energy bill and multi-dimensional environmental impacts. To counter these problems, a hybrid technique combining the evaporative cooling technique with a venturi-shaped natural ventilation tower is proposed. The evaporative cooling takes advantage of cooling in response to the wind blowing through a layer of wetted surface that is built with permeable materials. Combining with the specially designed venturi-shaped natural ventilation tower to improve the volume intake of wind externally, this system is aimed to reduce temperature and achieve thermal comfort by cooling down the air with circulation in a continuous accumulative mode. To gauge the efficiency and effectiveness of this hybrid technique, an evaporative system known as the Wind Induced Evaporative Cooling System (WIEC) is directly fed into a testing chamber (installed with sensors) fabricated with a scale of 1:6. The system was tested in a hot and humid climate with a temperature range of 27°C to 34°C. The finding shows that our system is able to reduce temperatures up to 3.873°C with an output cooling capacity of 9 W to 476.3 W, which shows the feasibility of this study.